The Influence of Family Environment on Physical Activity Participation Among College Students in Chongqing - Wang, JingRui; Wang, ShaoJie; Jiang, Bo; Shen, XingZhu (Quality in Sport, 2025)
As the primary institution where students receive their education, the family plays a prominent role in the physical and mental development of university students. This study situates the family environment as the broader context to analyze its impact on the participation of college students in Chongqing in physical activities. The research categorizes universities in Chongqing into three types—specialized institutions, comprehensive universities, and normal universities—and focuses on students from these categories as the subjects of investigation. Methods such as literature review, questionnaire surveys, and mathematical statistics were employed, with data analysis conducted using SPSS. The study concludes that the family environment has a significant positive influence on university students’ motivation to engage in physical activities. Specifically, the greater the level of family support for participation in sports, the stronger the motivation of students to take part in such activities. This research aims to assess the extent to which family environment affects physical activity participation among university students in Chongqing, with the goal of enhancing their motivation and autonomy in sports engagement. By starting from the foundational level of family education, it seeks to gradually increase the importance of physical education within China’s educational system and contribute to building a strong sporting nation.